CHEMICAL COMPOSITION OF ANIMAL HORSES (Conference Zone, 2022)
The acidity of chromtanide tanned leather is of practical interest in connection with the available data on the harmful effect of an increased acid content on the stability of leather during long-term storage. The acidity of the skin is judged by the concentration of hydrogen ions (pH) of the extract obtained by infusing a sample of crushed skin in a solution of potassium chloride; The pH of the potassium chloride extract is set electrometrically using special potentiometers.